Gambaran Penalaran Moral Siswa Sekolah Menengah Pertama - Wulan Lisnawati (Guidena)
Moral reasoning is a person's cognitive ability in considering decisions to determine an action. Moral reasoning is a predictor factor for juvenile delinquency, where the lower a person's moral reasoning, the higher the certainty of his delinquency. Kohlberg revealed that of a number of factors that can lead to juvenile delinquency, a high level of moral reasoning can serve as an obstacle to juvenile delinquency. Thus, to uncover actual moral behavior that can be traced through moral reasoning. This research is a descriptive quantitative research that aims to see the picture of moral reasoning in junior high school students. This research was conducted on 312 class VIII students of SMP Negeri 31 Bandung for the 2022/2023 Academic Year.